Molecular signatures of disulfidptosis: interplay with programmed cell death pathways and therapeutic implications in oncology - Yingchao Liu; Sainan Li; Yunyi Wu; Ping Zhang; Yanhua Yu; Xi Chen; Lingyan Yu; Xinyi Yang; Huanjuan Li; Cuiyun Wu; Jing Du; Yanchun Li (Cellular & Molecular Biology Letters)
Abstract Disulfidptosis represents a newly identified form of regulated cell death (RCD) distinct from other well-established RCD pathways. It occurs during periods of glucose starvation, specifically when intracellular NADPH is rapidly depleted and the expression of Solute Carrier Family 7 Member 11 (SLC7A11) is highly upregulated. Cancer cells utilize SLC7A11 to import cystine from the extracellular environment, and subsequently employ NADPH to convert it into cysteine. In the event of NADPH deficiency or an impairment in its utilization, cystine accumulates within the cells. This accumulation results in abnormal disulfide bond formation within actin cytoskeleton proteins, which in turn causes the collapse of the actin network and ultimately triggers disulfidptosis. This process uncovers a metabolic vulnerability within tumors, offering novel perspectives on the mechanisms that underlie cell death. In this paper, we provide a comprehensive review of the mechanism of disulfidptosis and compare its similarities and differences with other common programmed cell death mechanisms, such as apoptosis, autophagy, ferroptosis, and cuproptosis. The aim is to gain a more profound understanding of the characteristics and mechanisms of various cell death pathways. Understanding the correlation between disulfidptosis and tumors constitutes a crucial theoretical foundation for future research endeavors in cancer treatment. This review offers valuable insights that could pave the way for developing novel cancer treatment strategies and lead to groundbreaking advancements in cancer therapy.